Comparative Settlement of Labour Disputes in United States and Canada - Woods, H.W. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1954)
SummaryEmployers and unions in Canada are more and more being brought under a common code of behaviour with regard to disputes occurring after a contract is signed. Law makers have determined the shape or form and established the jurisdiction of the arbitration itself. After having given reference to the appropriate Canadian legislation for the settlement of disputes, the author turns to the United States and describes the composition and functioning of the American Arbitration Association. The last section of the article is devoted to the possible application in Canada of the principles and procedures of the American system concerning the settlement of justiciable disputes and account is taken of certain law and tradition differences existing in this country.